(untitled) (Journal of Pharmaceutical Negative Results, 2022)
In this paper, we measured the Macroeconomic Efficiency of Arab Countries by using Data Envelopment Analysis (DEA) during the period (2000 - 2020), to measure the efficiency of the overall economy of Arab countries by methodology of Technical Efficiency , Deterministic Frontier Approach by using Data Envelopment Analysis (DEA) according to the concepts of Constant Returns To Scale (CRS) and Variable Returns To Scale (VRS) to estimate both Technical Efficiency (TE), and Scale Efficiency (SE). This paper also deals about with the study of the impact of trade integration among Arab countries and Egypt on intra-agricultural trade between them, to determine the accession of countries to economic integration leads to an increase in the flow of foreign trade to countries among themselves through an increase in intra-regional exports, which leads to an increase in the volume of intra-regional trade of the integration countries and thus an increase in the self-sufficiency ratio of intra-trade goods.